A Method to Form Smooth Films of Liquid Metal Supported by Elastomeric Substrate. Issue 10 (9th August 2018) - Hirsch, Arthur; Lacour, Stéphanie P.
Abstract: Several methods are proposed to manipulate and pattern liquid metal films into elastic conductors but all lack precise control over the film thickness and roughness, thereby limiting its uniformity, stability, and reproducibility. Here, an approach relying solely on wetting phenomena is proposed to produce smooth film of liquid gallium (Ga) on extended surface areas with controlled thickness and electrical properties. The surface chemistry and topography of silicone rubber (poly(dimethylsiloxane)) is engineered with microstructured pillars and gold precoating layer to produce Ga superlyophilic substrates. Physical vapor deposition of Ga on such substrates leads to the formation of smooth and homogeneous films by imbibition of the surface topography rather than coalescence and formation of Ga drops. By capillarity, Ga accumulates in between the pillars up to their top surface, forming a smooth film with a root mean square roughness (Rq) smaller than 100 nm. The wetting conditions and electromechanical properties of the resulting films are compared based on the selection of the microtexture patterns and a model of the film sheet resistance as a function of the texture geometrical parameters is established. Abstract : Gallium (Ga) superlyophilic substrates are formed on silicone elastomer by combining surface microstructuring with gold film precoating. Physical vapor deposition of Ga on such substrate leads to the formation of a smooth and homogeneous film by imbibition of the surface topology. This approach enables control over the thickness and sheet resistance of the resulting liquid metal film.